PPARs as Key Mediators of Metabolic and Inflammatory Regulation - Vázquez-Carrera, Manuel; Wahli, Walter (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Mounting evidence suggests a bidirectional relationship between metabolism and inflammation. Molecular crosstalk between these processes occurs at different levels with the participation of nuclear receptors, including peroxisome proliferator-activated receptors (PPARs). There are three PPAR isotypes, α, β/δ, and γ, which modulate metabolic and inflammatory pathways, making them key for the control of cellular, organ, and systemic processes. PPAR activity is governed by fatty acids and fatty acid derivatives, and by drugs used in clinics (glitazones and fibrates). The study of PPAR action, also modulated by post-translational modifications, has enabled extraordinary advances in the understanding of the multifaceted roles of these receptors in metabolism, energy homeostasis, and inflammation both in health and disease. This Special Issue of IJMS includes a broad range of basic and translational article, both original research and reviews, focused on the latest developments in the regulation of metabolic and/or inflammatory processes by PPARs in all organs and the microbiomes of different vertebrate species.